2018
DOI: 10.32677/ijch.2018.v05.i07.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of cord blood and maternal lipid profiles

Abstract: Objectives: The objectives of this study were to study the cord blood lipid profile in neonates in relation to maternal preconceptional body mass index (BMI), maternal glucose intolerance, maternal lipid profile, family history of metabolic syndrome, intrauterine fetal growth, and birth weight of baby. Methodology: It was a prospective cohort study and was carried out in Pondicherry Institute of Medical Sciences over a period of 1 year. The sample size estimated was 150 mother-infant pairs. Informed consent wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…4 In a study by Nita Mariam Abraham et al, no association was found between cord blood and maternal lipid profiles. 9 Shahla Vaziri Esfarjani et al, studied the influence of maternal age on the cord lipid profile and found that there is a statistically significant negative correlation between cord blood HDL-C and maternal age (p <0.01). 10 A study by Juárez IE et al, concluded that there is an association between lipid levels in mothers and their children.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a study by Nita Mariam Abraham et al, no association was found between cord blood and maternal lipid profiles. 9 Shahla Vaziri Esfarjani et al, studied the influence of maternal age on the cord lipid profile and found that there is a statistically significant negative correlation between cord blood HDL-C and maternal age (p <0.01). 10 A study by Juárez IE et al, concluded that there is an association between lipid levels in mothers and their children.…”
Section: Discussionmentioning
confidence: 99%